2021
DOI: 10.1111/ppe.12739
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of stillbirth trends over two decades in Wales, United Kingdom and Western Australia: An international retrospective cohort study

Abstract: Background: Stillbirth is a critical public health issue worldwide. While the rates in high-income countries are relatively low, there are persistent between-country disparities.Objectives: To compare stillbirth rates and trends in Wales and the State of Western Australia (WA), Australia, and provide insights into any differences. Methods:In this international retrospective cohort study, we pooled populationbased data collections of all births ≥24 weeks' gestation (excluding terminations for congenital anomali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 38 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…While our study showed declining early gestation stillbirth and neonatal death rates, there are conflicting findings on trends in early gestation stillbirths and neonatal deaths, particularly across gestational age groups. A Western Australian study found no evidence of a trend in the stillbirth rates at 24–27 weeks gestation during 1993–2015, while another reported a declining trend in the stillbirth rates among singleton births at 20–27 weeks in the same state during 1986–2010 7,8 . No change in the neonatal death rate among singletons at <24 weeks gestation was reported during 1988–2017 in Queensland, although rates decreased at 24–27 weeks; however, pregnancy terminations were included in these analyses 17 .…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…While our study showed declining early gestation stillbirth and neonatal death rates, there are conflicting findings on trends in early gestation stillbirths and neonatal deaths, particularly across gestational age groups. A Western Australian study found no evidence of a trend in the stillbirth rates at 24–27 weeks gestation during 1993–2015, while another reported a declining trend in the stillbirth rates among singleton births at 20–27 weeks in the same state during 1986–2010 7,8 . No change in the neonatal death rate among singletons at <24 weeks gestation was reported during 1988–2017 in Queensland, although rates decreased at 24–27 weeks; however, pregnancy terminations were included in these analyses 17 .…”
Section: Discussionmentioning
confidence: 85%
“…However, a declining trend in these rates has not been consistently observed across all late gestation age groups . S tatistically significant decreases in the stillbirth rate at 28–31 weeks were reported in Wales during 1993–2015, but not at 32–36, 37–38 and 39–41 weeks 7 . In the United Kingdom, neonatal death rates decreased from 2015 to 2019 at 28–31, 32–36 and 37–41 weeks, but increased at ≥42 weeks 10 .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This reflects, in itself, the lack of priority given to stillbirth as a public health problem, but also the paucity of high‐quality routine population birth data in many countries and the complicated politics of defining the lower threshold for viability for recording births and of creating clear registration guidelines for pregnancy terminations, which are commonly registered as stillbirths. In this context, the study by Bailey et al 2 in this issue of Paediatric and Perinatal Epidemiology , which optimises existing data on stillbirths to explore trends and risk factors in countries with similar standards of living and access to health services, is valuable.…”
Section: Figurementioning
confidence: 99%